Analysis of challenges and proposal of method for data integration in APS software - Fernandes, Daniely Ferreira; Lemos, Luana Falquetto; Torres, Henrique Bertochi; Moura, Luciano Raizer; Gomes, Thiara Cezana (Brazilian Journal of Production Engineering, 2025)
This study investigates key challenges in implementing Advanced Planning and Scheduling (APS) systems in a factory context, with a specific focus on data integration. Through interviews and questionnaires conducted with a software company and its clients, we identified several critical obstacles. The findings revealed persistent issues, such as data inconsistencies, poor adaptability of information to the systems, and a lack of active engagement from the Information Technology (IT) team. Based on this analysis, the Data Integration Method (DIM) is proposed. The DIM is designed to simplify integration and mitigate these identified challenges, ultimately ensuring a more fluid and effective implementation of APS systems
Keywords: Advanced Planning and Scheduling; APS Software; Opcenter APS; Production Planning and Control; APS Implementation Projects; Data Integration with APS